Canadian copyright law - Harris, Lesley Ellen (John Wiley & Sons, Inc., 2014)
"The fourth edition of Canadian Copyright Law brings you the latest updates according to new Canadian legislation and international agreements. Copyright infringement has always been illegal. Today with near-constant access to the internet and the mainstream explosion of digital formats, copyright is one of the most important issues for creative professionals, consumers of that media, and those who work in related industries. The line between what is protected and what is "free" is blurring further, and the copyright issues are more complex then ever"–Book jacket.